PENGARUH MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM DAN SOAL TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA - Dian Kurniati Agusningtiah; Liknin Nugraheni (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2023)
The purpose of this study was to determine whether the cooperative learning model of sending greetings and questions technique with conventional learning has an effect on students' mathematics learning outcomes on the material of rows and series. This type of research uses quantitative research and the method used is the experimental method. Class X Phase E3 and Phase E4 were used in the sample of this study. The test technique was used in the collection technique in this study, by analyzing through the t-test hypothesis, using the prerequisite test: normality test, and homogeneity test. From the prerequisite calculations it can be concluded that both data are normally distributed and vary equally, then proceed with hypothesis testing or t-test. Posttest results with row and sequence material, there is a significant difference. The test scores obtained by using the cooperative learning model of sending greetings and questions technique in the Phase E3 class averaged 86.83, while the test scores carried out with the conventional learning model in the Phase E4 class obtained an average of 78.19. Based on the results, sig. (two-way) 0.000 <0.05, it is concluded that there is an influence on student learning outcomes when the cooperative learning model of the greeting and question technique is applied to mathematics learning in the experimental class compared to applying conventional learning in the control class.